Craniofacial morphology and dental maturity in children with reduced somatic growth of different aetiology and the effect of growth hormone treatment - Sotiria Davidopoulou; Athina Chatzigianni (SpringerOpen, 2017)
Abstract Children with reduced somatic growth may present various endocrinal diseases, especially growth hormone deficiency (GHD), idiopathic short stature (ISS), chromosomal aberrations, or genetic disorders. In an attempt to normalize the short stature, growth hormone (GH) is administered to these children. The aim of this literature review was to collect information about the craniofacial morphology and dental maturity in these children and to present the existing knowledge on the effect of GH treatment on the above structures. This review demonstrated that regardless of the origin of the somatic growth retardation, these children show similar craniofacial features, such as short length of the cranial base and the mandible, increased lower facial height, retropositioned mandible, and obtuse gonion angle. On the other hand, dental maturation does not demonstrate a specific pattern. Except for the above findings, muscle alterations seem to be present in individuals with short stature, who present low body muscle mass and strength, while studies on their craniofacial muscles seem to be lacking. After GH administration, the exact amount and pattern of craniofacial growth is unpredictable; however, the facial convexity decreases, mandibular length increases, and posterior facial height increases, while tooth eruption remains unaffected. Thus, it is of great importance to gain more insight into the craniofacial growth of treated and untreated children with reduced somatic growth so that the influence of GH therapy on the various craniofacial structures could be ascertained and proper orthodontic treatment could be selected.